2021
DOI: 10.1016/j.xcrm.2021.100425
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transcriptome identifies progressive markers and potential therapeutic targets in chronic myeloproliferative neoplasms

Abstract: Predicting disease progression remains a particularly challenging endeavor in chronic degenerative disorders and cancer, thus limiting early detection, risk stratification, and preventive interventions. Here, profiling the three chronic subtypes of myeloproliferative neoplasms (MPNs), we identify the blood platelet transcriptome as a proxy strategy for highly sensitive progression biomarkers that also enables prediction of advanced disease via machine-learning algorithms. The MPN platelet transcriptome reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 93 publications
(172 reference statements)
3
32
0
Order By: Relevance
“…The copyright holder for this preprint this version posted December 11, 2022. ; https://doi.org/10.1101/2022.12.08.519689 doi: bioRxiv preprint A recent large-scale gene expression profiling of platelets from MPN patients suggested the activation of OXPHOS and mTORC1 signaling pathways in all three subtypes of MPNs 33 . Importantly, these differentially expressed genes robustly predict MPN progression, highlighting the importance of platelet biology in MPNs 33 . Our proteomics data validated the activation of OXPHOS and mTORC1 proteins in platelet from MPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted December 11, 2022. ; https://doi.org/10.1101/2022.12.08.519689 doi: bioRxiv preprint A recent large-scale gene expression profiling of platelets from MPN patients suggested the activation of OXPHOS and mTORC1 signaling pathways in all three subtypes of MPNs 33 . Importantly, these differentially expressed genes robustly predict MPN progression, highlighting the importance of platelet biology in MPNs 33 . Our proteomics data validated the activation of OXPHOS and mTORC1 proteins in platelet from MPN.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale gene expression profiling of platelets from MPN patients suggested the activation of OXPHOS and mTORC1 signaling pathways in all three subtypes of MPNs 33 . Importantly, these differentially expressed genes robustly predict MPN progression, highlighting the importance of platelet biology in MPNs 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Gorbenko [117] JAK2 V617F allele burden qRT-PCR 24 -Correlation between leukocyte DNA and platelet mRNA: R = 0.79, R 2 = 0.62; changes in platelet RNA preceded changes in leukocyte DNA Shen [118] 3326 genes RNA-seq 95 21 The progressive transcriptome model in the classification of 24 essential thrombocythemias, 33 polycythemia vera, and 40 myelofibrosis: AUC = 0.97 Thyroid neoplasm Shen [119] 765 genes RNA-seq 42 27 Ac = 97%; AUC = 0.998. The average Ac for the diagnosis of thyroid adenomas, papillary thyroid cancer and metastasized papillary thyroid cancer was 80.5% Prostate cancer…”
Section: Myeloproliferative Neoplasmsmentioning
confidence: 99%
“…However, this study was primarily in mice and remains to be confirmed in independent additional MPN models and patient-derived specimens. Our recent investigation, profiling the blood platelet transcriptome in all three subtypes of MPN patients 20 identified high expression of genes and pathways associated with impaired proteostasis, ER stress and unfolded protein response (UPR) well-recognized in other age-related disorders 21-25 . Here, we extend our prior MPN patient platelet transcriptomic data with a focus on genes associated with proteostasis, cell proliferation, ER stress or calcium signaling at high statistical significance (FDR <0.01), and representing four types of trends in platelet RNA expression across MPN subtypes: progressively downregulated, progressively upregulated, consistently upregulated, and uniquely upregulated in MF alone.…”
Section: Introductionmentioning
confidence: 99%